Microbial metabolism and bio-cement formation in extreme cementitious environments - Tiwari, Sakshi (Curtin University, 2022)
Using the principles of biomineralization and Microbially Induced Carbonate Precipitation, an attempt has been made to improve its application in marine concrete environments. Microbial dynamics under highly alkaline and saline marine concrete environments of pH> 11 and 5% salinity were studied to isolate extremophilic strains with higher viability, metabolic activity, and biomineralizing abilities to work in harsh concrete environments. They were used as isolates and co-cultures with a standard lab strain for comparison.